The OEIS is supported by the many generous donors to the OEIS Foundation.

 Year-end appeal: Please make a donation to the OEIS Foundation to support ongoing development and maintenance of the OEIS. We are now in our 59th year, we have over 358,000 sequences, and we’ve crossed 10,300 citations (which often say “discovered thanks to the OEIS”). Other ways to Give
 Hints (Greetings from The On-Line Encyclopedia of Integer Sequences!)
 A317800 G.f. A(x) satisfies: Sum_{n>=1} ( A(x) - (-1)^n * A(-x) )^n * (-1)^n / n = 0. 2

%I

%S 1,1,1,4,10,33,105,354,1214,4206,14846,52750,189516,686745,2506913,

%T 9211226,34036230,126426446,471769950,1767460752,6645539212,

%U 25076120890,94937019050,360268374124,1369645176012,5226326126048,20039843858208,76654036799842,290534140464144,1123489897863753,4582416833711249,17212665701732282,45565498032190230

%N G.f. A(x) satisfies: Sum_{n>=1} ( A(x) - (-1)^n * A(-x) )^n * (-1)^n / n = 0.

%C Odd terms occur at a(2^k - 1) and a(2^k - 2) for k > 1 and at a(1), while a(n) is even elsewhere (conjecture).

%C First negative term is a(37).

%H Paul D. Hanna, <a href="/A317800/b317800.txt">Table of n, a(n) for n = 1..520</a>

%F G.f. A(x) satisfies:

%F (1) A(-A(-x)) = x.

%F (2a) Sum_{n>=1} ( A(x) - (-1)^n * A(-x) )^n * (-1)^n / n = 0.

%F (2b) A(A(x)) = B(x) such that Sum_{n>=1} ( x + (-1)^n * B(x) )^n / n = 0, where B(x) is the o.g.f. of A316363.

%F (3a) A(A(x)) = -x + 2 * Series_Reversion( x - x^2/(1 - 2*x^2) ).

%F (3b) A(A(x)) = x + 2 * Series_Reversion( x/sqrt(1 + 2*x^2) - x^2 )^2.

%F Let C = (A(x) + A(-x))/2 and S = (A(x) - A(-x))/2, then

%F (4a) arctanh(2*C) + log(1 - 4*S^2)/2 = 0,

%F (4b) 1 - 4*S^2 = (1 - 2*C)/(1 + 2*C),

%F (5a) S^2 = C/(1 + 2*C),

%F (5b) C = S^2/(1 - 2*S^2),

%F (6a) A(x) = S + S^2/(1 - 2*S^2),

%F (6b) A(x) = C + sqrt(C/(1 + 2*C)).

%F (7) 0 = (2*y + y^2 - y^3) - (2 - 2*y + y^2)*A(x) + (1 + y)*A(x)^2 + A(x)^3, where y = -A(-x) = Series_Reversion(A(x)).

%e G.f. A(x) = x + x^2 + x^3 + 4*x^4 + 10*x^5 + 33*x^6 + 105*x^7 + 354*x^8 + 1214*x^9 + 4206*x^10 + ...

%e Let the series bisections of g.f. A(x) be denoted by

%e C = (A(x) + A(-x))/2 = x^2 + 4*x^4 + 33*x^6 + 354*x^8 + 4206*x^10 + ...

%e S = (A(x) - A(-x))/2 = x + x^3 + 10*x^5 + 105*x^7 + 1214*x^9 + 14846*x^11 + ...

%e then from the definition we have

%e 0 = (2*C) - (2*S)^2/2 + (2*C)^3/3 - (2*S)^4/4 + (2*C)^5/5 - (2*S)^6/6 + (2*C)^7/7 - (2*S)^8/8 + ...

%e thus arctanh(2*C) + log(1 - 4*S^2)/2 = 0,

%e so that (1 - 2*C)/(1 + 2*C) = 1 - 4*S^2.

%e RELATED SERIES.

%e A(A(x)) = x + 2*x^2 + 4*x^3 + 14*x^4 + 52*x^5 + 204*x^6 + 840*x^7 + 3574*x^8 + 15588*x^9 + 69332*x^10 + ... + A316363(n)*x^n + ...

%e where A(A(x)) = -x + 2 * Series_Reversion( x - x^2/(1 - 2*x^2) ).

%o (PARI) /* From: A(x) = S + S^2/(1 - 2*S^2) and A(x) = Series_Reversion(-A(-x)) */

%o {a(n) = my(A=[1,1],S); for(i=1,n, S=(x*Ser(A) - subst(x*Ser(A),x,-x))/2; A=concat(Vec( S + S^2/(1 - 2*S^2) ),0); if(#A%2==1,A = (A + Vec( serreverse(subst(-x*Ser(A),x,-x)) ) )/2 ); );A[n]}

%o for(n=1,30, print1(a(n),", "))

%Y Cf. A316363.

%K sign

%O 1,4

%A _Paul D. Hanna_, Aug 09 2018

Lookup | Welcome | Wiki | Register | Music | Plot 2 | Demos | Index | Browse | More | WebCam
Contribute new seq. or comment | Format | Style Sheet | Transforms | Superseeker | Recents
The OEIS Community | Maintained by The OEIS Foundation Inc.

Last modified December 2 13:44 EST 2022. Contains 358510 sequences. (Running on oeis4.)